THE ROLE OF MULTISENSORY MARKETING ON CUSTOMER LOYALTY OF CONVENIENCE STORES - Budiarti, Lina; Rena Feri Wijayanti; Win Narasuci; Tirto Unarto (Magister Manajemen Universitas Islam Malang, 2025)
Multisensory marketing is an interesting topic to be studied further amidst the increasingly competitive market for customer retention. It involves the five senses of customers: visual marketing to pamper the sense of sight, auditory marketing by providing sound or tone for the sense of hearing, olfactory marketing as an effort to stimulate the sense of smell, tactile marketing for the sense of touch, and gustatory marketing to provide an experience for the sense of taste. Multisensory marketing can be applied not only to the service sector, but also to other sectors, such as the retail industry, especially convenience stores. This study aims to investigate the role of multisensory marketing on customer loyalty in the context of the convenience store retail sector in Malang City, East Java, Indonesia. To achieve the research objectives, a quantitative approach was used through a questionnaire. A total of 214 questionnaires were distributed, collected, and analyzed from customers of FamilyMart and K3Mart convenience stores in Malang City. Multiple regression analysis was employed to investigate the research model. The results show that auditory, olfactory, and gustatory marketing had a significant influence on customer loyalty, while visual and tactile marketing did not have a significant influence.